Secondary Infections in Critically Ill Patients with COVID-19: A Retrospective Study - Luca Caiazzo; Chiara Temperoni; Benedetta Canovari; Oriana Simonetti; Roberto Montalti; Francesco Barchiesi (MDPI AG, 2022)
Patients with severe COVID-19, especially those followed in the ICU, are at risk for developing bacterial and fungal superinfections. In this study, we aimed to describe the burden of hospital-acquired superinfections in a cohort of consecutive, severe COVID-19 patients hospitalized between February and May 2021 in the intensive care unit (ICU) department of San Salvatore Hospital in Pesaro, Italy. Among 89 patients considered, 68 (76.4%) acquired a secondary infection during their ICU stay. A total of 46 cases of ventilator-associated pneumonia (VAP), 31 bloodstream infections (BSIs) and 15 catheter-associated urinary tract infections (CAUTIs) were diagnosed. Overall mortality during ICU stay was 48%. A multivariate analysis showed that factors independently associated with mortality were male gender (OR: 4.875, CI: 1.227-19.366, p = 0.024), higher BMI (OR: 4.938, CI:1.356-17.980, p = 0.015) and the presence of VAP (OR: 6.518, CI: 2.178-19.510, p = 0.001). Gram-negative bacteria accounted for most of the isolates (68.8%), followed by Gram-positive bacteria (25.8%) and fungi (5.3%). Over half of the infections (58%) were caused by MDR opportunistic pathogens. Factors that were independently associated with an increased risk of infections caused by an MDR pathogen were higher BMI (OR: 4.378, CI: 1.467-13.064, p = 0.0008) and a higher Charlson Comorbidity Index (OR: 3.451, 95% CI: 1.113-10.700, p = 0.032). Secondary infections represent a common and life-threatening complication in critically ill patients with COVID-19. Efforts to minimize the likelihood of acquiring such infections, often caused by difficult-to-treat MDR organisms-especially in some subgroups of patients with specific risk factors-must be pursued.